Leaders without ethics in global business: corporate psychopaths - Boddy, C.; Ladyshewsky, Richard; Galvin, Peter (John Wiley & Sons, Ltd., 2010)
This paper introduces the concept of Corporate Psychopaths as ruthless employees who can successfully gain entry to organizations and can then get promoted within those organizations to reach senior managerial and leadership positions. What little empirical research currently exists supports the view that Corporate Psychopaths are more commonly found at senior levels of organizations. This paper presents further empirical evidence that supports this view. It discusses how, in a quantitative sample of 346 whitecollar workers, in 2008, research using a psychopathy scale identified greater levels of psychopathy at more senior levels of corporations than at more junior levels. The paper goes on to propose that this is a universal issue that can pose various ethical problems for corporations because of the ruthless, selfish and conscience-free approach to life that Corporate Psychopaths have. Other ethical issues are to do with their moral accountability and with the problems associated with the possibility of screening employees for psychopathy. The paper reviews the literature on psychopathy and concludes that while psychopaths appear to be universal in occurrence, they may well be environmentally limited in their possible actions in more collectivist societies. However, the global spread of western, individualistically oriented corporations may pose a threat to any collectivistsocieties in which they operate.